The princess diaries Mia tells it like it is - Cabot, Meg. (New York : Avon books, 2004)
presents the first two volumes of the Princess Diaries series, in which fourteen-year old Mia learns of her royal lineage and tries to cope with the news.
920
Accelerated Reader AR
Keywords: Princesses -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Diaries -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction